Pengaruh Variasi Dosis Tawas dan Debit pada Penjernih Air Multifilter Sarang Tawon terhadap Kekeruhan - Kumala, Fioniselly Djocie; Jaya, Allan Restu; Nindito, Dwi Anung (Universitas Trunojoyo Madura, 2025)
The increase in population in peat swamp areas, especially in Central Kalimantan, has led to an increase in the demand for clean water for household needs and daily activities. The geographical conditions of peat swamps cause river water to become turbid due to sedimentation. Several efforts to purify water have been made, including the use of coagulation and filtration methods. This study aims to determine the effect of alum dose variation and water discharge on turbidity parameters, which were tested using the Sarang Tawon multifilter water treatment. The experimental method was used to test the Sarang Tawon multifilter water treatment, which combines alum as a coagulant with filtration media in the form of coral chips, ferrolite, and silica sand. The alum dose variations used were the normal alum dose (per volume of water), half and twice the normal alum dose, using four variations of water discharge. The results showed that alum, used as a coagulant in the Sarang Tawon multifilter water treatment, can significantly reduce turbidity parameters. The use of half of the alum dose with low water discharge is more optimal in reducing turbidity parameters, which is 66.376%. The significance of this research lies in the potential for using the Sarang Tawon multifilter water treatment with optimized water discharge settings to reduce the need for alum. The use of half a dose of alum at low water discharge can yield results comparable to using twice the dose of alum at high discharge. Further research recommendations may utilise pyrite water as a source of raw water, which is commonly found in peatlands.